Tyrrhenian Upper Waters in the Ustica Island (Marine Protected Area, Sicily, Italy). (21st June 2009) - Sanfilippo, Marilena; Pulicanò, Giuseppa; Manganaro, Antonio; Reale, Alessandra; Cortese, Giuseppa
Abstract : The Marine Protected Area (MPA) of Ustica was monitored for the hydrographic properties in the A zone of the reserve during the period from the autumn of 2001 to the winter of 2003. This study is also a part of a great triennal project (2001–2004) "Sistema Afrodite", that was carried out in all the MPAs instituted in Italy. The parameters examined were treated statistically to show their seasonal variability. Temperature, nitrate, phosphate, and chlorophyll a showed similar trends between winter 2002 and 2003, while differences between winter 2002 and 2003 were noticed for salinity, dissolved oxygen, and silicate. It is postulated that the Atlantic current and eddies along its margin result in variation of the water characteristics in the MPA zone analyzed in this study.